Tissue-specific Calibration of Real-time PCR Facilitates Absolute Quantification of Plasmid DNA in Biodistribution Studies - Joan K Ho; Paul J White; Colin W Pouton (Elsevier, 2016)
Analysis of the tissue distribution of plasmid DNA after administration of nonviral gene delivery systems is best accomplished using quantitative real-time polymerase chain reaction (qPCR), although published strategies do not allow determination of the absolute mass of plasmid delivered to different tissues. Generally, data is expressed as the mass of plasmid relative to the mass of genomic DNA (gDNA) in the sample. This strategy is adequate for comparisons of efficiency of delivery to a single site but it does not allow direct comparison of delivery to multiple tissues, as the mass of gDNA extracted per unit mass of each tissue is different. We show here that by constructing qPCR standard curves for each tissue it is possible to determine the dose of intact plasmid remaining in each tissue, which is a more useful parameter when comparing the fates of different formulations of DNA. We exemplify the use of this tissue-specific qPCR method by comparing the delivery of naked DNA, cationic DNA complexes, and neutral PEGylated DNA complexes after intramuscular injection. Generally, larger masses of intact plasmid were present 24 hours after injection of DNA complexes, and neutral complexes resulted in delivery of a larger mass of intact plasmid to the spleen.